Urgensi Etika bagi Komunikasi Politik - Michael Carlos Kodoati (Sekolah Tinggi Filsafat Seminari Pineleng, 2023)
The writing aims to observe the urgency of ethics for political communication. Through literature research on Brian McNair's thought, one crucial question is revealed, is the increasing role of mass communication in the political process